Methodological guide for the implementation of interactive virtual tours for adolescents through photogrammetry as a means of accessing cultural heritage - Yucra Limahuay, Willy D. (2022)
Nowadays, there is a need to facilitate access to cultural heritage for teenagers, who are looking for new experiences but see museums as repositories of antiques. Therefore, in this research, a methodological guide was defined for the implementation of virtual tours through the photogrammetry technique, which contains four stages that specify the step by step for the implementation of a virtual environment containing complements such as audio guide, an interactive location map, 3D pieces and displacement points to move within the environment. To corroborate the validity of the product, surveys were conducted for adolescents between 12 and 16 years old, verifying the increased interest in learning about culture and interest in the use of virtual tours, achieving access to cultural heritage in a virtual environment, it should be noted that the virtual tours do not seek to replace the visit to museums, on the contrary, it offers an alternative as a technological tool that promotes the visit to museums, facilitating access, generating curiosity, learning and appreciation of our cultural wealth in adolescents.